The Icefield Ranges Research Project, 1970 - Ragle, Richard H.; Marcus, Melvin G.; Houston, Charles S. (ARCTIC, 1971)
In 1970 the Icefield Ranges Research Project (IRRP) conducted its tenth consecutive summer of interdisciplinary basic research in the St. Elias Mountains, Yukon Territory, and in the valley and plateau region to the east where all aspects of the environment reflect the influence of those mountains. Summer field investigations began in April and ended the last week in August. And for the first time since the Project's inception in 1961, two programs have continued through the winter (1970-71). This opportunity to continue studies all the year round was made possible by the winterization of a log house; the work, begun in 1967 on the north side of the runway near the Kluane Base Camp, was completed with modern facilities in June 1970. This short paper briefly reviews the programs which were accomplished during the 1970 field season within the broad categories of glaciology, geophysics, physical geography, biology, and human physiology.